Nanomaterials for Autophagy-Related miRNA-34a Delivery in Cancer Treatment - Sharma, Priyanka; Dando, Ilaria; Strippoli, Raffaele; Kumar, Suresh; Somoza, Alvaro; Cordani, Marco; Tafani, Marco (Frontiers in Pharmacology, 2020)
Autophagy is an evolutionary conserved physiological process with a fundamental role during development, differentiation, and survival of eukaryotic cells. On the other hand, autophagy dysregulation is observed in many pathological conditions, including cancer. In particular, tumor growth and progression are accompanied and promoted by increased autophagy that allows cancer cells to escape apoptosis and to proliferate also in harsh microenvironments. It is, therefore, clear that the impairment of the autophagic process may represent a valid strategy to inhibit or reduce cancer growth and progression. Among the plethora of molecular players controlling cancer growth, a group of small endogenous non-coding RNAs called microRNA (miRNAs) has recently emerged. In fact, miRNAs can act as both oncogenes or oncosuppressors depending on their target genes. Moreover, among miRNAs, miRNA-34a has been connected with both tumor repression and autophagy regulation and its expression is frequently lost in many cancers. Therefore, enforced expression of miRNA-34a in cancer cells may represent a valid strategy to reduce cancer growth. However, such strategy is limited by the fast biodegradation and short half-life of miRNA-34a and by the lack of an efficient intracellular delivery system. The following review describes the autophagic process and its role in cancer as well as the role of miRNAs in general and miRNA-34a in particular in regulating tumor growth by modulating autophagy. Finally, we describe the use of nanoparticles as a promising strategy to selectively deliver miRNA-34a to tumor cells for therapeutic and diagnostic purposes.